2015
DOI: 10.1074/jbc.m114.598219
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Post-translational Modification of Nucleolin, SUMOylation at Lys-294, Mediates Arsenite-induced Cell Death by Regulating gadd45α mRNA Stability

Abstract: Background: Nucleolin is a multifunctional protein, but nucleolin-SUMO is unexploited. Results: Nucleolin-SUMO at Lys-294 facilitated binding with mRNA substrate gadd45␣ by maintaining its nuclear localization during cellular response to arsenite exposure. Conclusion: Nucleolin-SUMO promoted arsenite-induced apoptosis by increasing GADD45␣ expression. Significance: We identified a new modification of nucleolin and its contribution to the functional paradigm of nucleolin in mRNA stability regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 77 publications
0
43
1
Order By: Relevance
“…It has been reported the control of protein expression through mRNA stability in calcium signalling [50]. Zhang et al observed that SUMOylation of Nucleolin at K294 mediated cell death by regulating gadd45 mRNA stability [51]. 3-UTR mRNA pull-down assays and Western blot analysis indicated that the AU binding protein AUF1 interacted with the SERCA2a 3-UTR, which affected mRNA stability [52].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported the control of protein expression through mRNA stability in calcium signalling [50]. Zhang et al observed that SUMOylation of Nucleolin at K294 mediated cell death by regulating gadd45 mRNA stability [51]. 3-UTR mRNA pull-down assays and Western blot analysis indicated that the AU binding protein AUF1 interacted with the SERCA2a 3-UTR, which affected mRNA stability [52].…”
Section: Discussionmentioning
confidence: 99%
“…In light of these observations, several hypotheses can be proposed. NCL and NPM1 are both proteins that carry a high number of post-translational modifications, and evidence continues to accumulate suggesting that the nucleoplasmic translocation of both NCL (Kim et al 2005;Zhang et al 2015) and NPM1 (Liu et al 2006;Liu et al 2007;Sato et al 2004;Yogev et al 2008) may be regulated by multiple independent modifications and pathways in response to different genotoxic stresses or in distinct cell types. Moreover, the fact that NPM1 localization to DSBs could only be detected using an antibody recognizing the phosphorylated NPM1-pT199 suggests that any stress-induced relocalization of NPM1, and potentially NCL, may involve a small and specifically-modified population of these highly abundant proteins, and that such fractional relocalization may be unobservable with the currently D r a f t 32 available assays.…”
Section: Nucleoplasmic Translocation: a Mechanism Of Recruitment Or mentioning
confidence: 99%
“…In contrast, NCL binding to and stabilization of a defined G-quadruplex structure within the c-MYC gene promoter contributes to transcriptional repression of this locus, possibly by abolishing binding sites for activating TFs or altering the local chromatin (González et al 2009;González and Hurley 2010). Post-transcriptionally, NCL binding to mRNAs may effect expression of particular proteins, with NCL binding to the p53 mRNA 5'UTR resulting in translational activation, while its binding to gadd45α mRNA in response to arsenite treatment and K294-SUMOylation blocks the degradation of this transcript (Takagi et al 2005;Zhang et al 2015). Remarkably, NCL has even been reported to be constitutively displayed on the cell surface, where it may act as a ligand for particular growth-regulatory ligands and viruses (Fujiki et al 2014;Hovanessian et al 2010;Nisole et al 2002).…”
Section: Ncl Throughout the Cell -Nucleolus Nucleoplasm Cytoplasm Amentioning
confidence: 99%
“…Based on our previous finding that the IL-6 SRE required binding by a complex of cellular proteins including NCL, we mined a published RNAseq dataset for transcripts that were not depleted in SOX expressing 293T cells and were known to be bound by NCL [22,[49][50][51]. A transcript that fit these criteria was growth arrest and DNA damage-inducible 45 beta (GADD45B).…”
Section: Gadd45b Mrna Is Also Resistant To Sox-induced Degradationmentioning
confidence: 99%